Centenary from a Specific Angle: Reflections on Modern Irish Literature and the Irish Spirit in the Hungarian Literary Journal Nyugat (1908-1941) - Vöő, Gabriella (FOCUS: Papers in English Literary and Cultural Studies, 2024)
Early in the twentieth century Hungarian interest in English literature was part of a more general aspiration of intellectuals to absorb and draw inspiration from the culture of Western Europe, especially from English and continental Modernism. In January 1908 critics and editors Miksa Fenyő, Ernő Osvát, and Hugó Ignotus launched the semi-monthly literary periodical Nyugat, the centenary of which we now celebrate. The journal became a leading forum of literary Modernism in pre- and interwar Hungary, its name, “The West,” signalling the commitment of its editors and authors to join the aesthetic and intellectual ferment of Western Europe. The editors intended to overcome the belatedness and peripheral position of Hungarian literary culture in respect to European modernity. From the outset, the majority of the authors publishing in the journal were inspired by such tum-of-the-century European literary trends and movements like symbolism, aestheticism, and impressionism. Among the Hungarian literary journals of the time Nyugat represented the liberal, cosmopolitan orientation along with a restrained, balanced nationalism.